Electrical characterization of silicon PV-cell: modeling (vol 130, 379, 2024) - Yahyaoui, Nejmeddine; Mansouri, Salaheddine; Al-Sehemi, Abdullah G.; Dere, A.; Al-Ghamdi, A.; Yakuphanoğlu, Fahrettin (Springer Heidelberg, 2024)
[Abstract Not Available]